1986
DOI: 10.1017/s0022029900024614
|View full text |Cite
|
Sign up to set email alerts
|

Effects on mastitis of overmilking in conjunction with pulsation failure

Abstract: Half-udder comparisons were made using 56 cows for 2 months, in an experiment involving high bacterial challenge, to assess the combined effects of 5 min overmilking and pulsation failure (resulting from the use of shortened teatcup liners) on teat condition and mastitis. Only three new infections were confirmed in over 12500 quarter milkings in quarters milked with control liners (of 148 mm effective length) indicating little or no effect of prolonged overmilking in these quarters. A 3 -5-fold increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…In conclusion, it was apparent that, with the exception of SCC, all the udder health parameters considered in this study showed a consistent pattern, which was largely in agreement with the findings of Mein et al (1983Mein et al ( , 1986. The deep penetration of the fore teats into the teatcup liner together with long milking times adversely affects the health of the fore quarters.…”
Section: Clinical Mastitissupporting
confidence: 88%
See 2 more Smart Citations
“…In conclusion, it was apparent that, with the exception of SCC, all the udder health parameters considered in this study showed a consistent pattern, which was largely in agreement with the findings of Mein et al (1983Mein et al ( , 1986. The deep penetration of the fore teats into the teatcup liner together with long milking times adversely affects the health of the fore quarters.…”
Section: Clinical Mastitissupporting
confidence: 88%
“…The correlation between teat end hardness score and teat penetration at end of milking for fore teats was highly significant implying that reduced, or total lack of, massage on the teat end at the end of milking increased the teat end hardness. These results are consistent with those of Mein et al (1983Mein et al ( , 1986. Hamann (1987) postulated that increasing hyperkeratosis and teat end stiffness (both closely related to teat end hardness) over a certain level gave rise to increasing infection risk.…”
Section: Morphological Changes In Teatssupporting
confidence: 85%
See 1 more Smart Citation
“…) finds that a combination of higher vacuum level and lower level of cluster detachment leads to a more prominent prolongation of the teat canal and widening of teat diameter. Conversely, almost no effect of prolonged milking in quarters was observed when using a liner that provided a massage on the whole teat (Mein et al, 1986). Another fact that should be considered is that overmilking is milk flow dependent.…”
Section: Overmilkingmentioning
confidence: 98%
“…Natzke (1978) concluded that if overmilking is associated with mastitis its effects appear to be small. A detrimental effect of overmilking on new infection rate has only been shown in conjunction with pulsation (Mein et al 1986). However, 0steras & Lund (1988 found a significantly higher frequency of Staphylococcus aureus mastitis in herds with highline milking practising > 1 min overmilking.…”
Section: Udder Healthmentioning
confidence: 99%